KINERJA GURU PENJASORKES SEKOLAH DASAR YANG TERSERTIFIKASI PADA KECAMATAN BUMIAYU KABUPATEN BREBES TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine how the performance of elementary school teachers are certified Physical Education on Brebes Brits District in 2013. This study uses a quantitative research approach, data collection techniques were performed using questionnaires and documentation. Sampling technique using purposive sampling techniques although data analysis using descriptive statistics. The results are as follows: (1) Planning Learning conducted by a Certified elementary teacher Physical Educatiaon in Bradford County District Brits are good with a percentage of 84.1%, (2) Implementation Study conducted by the Certified elementary teacher Physical Education the Brits District Brebes been good with percentages 83.7%, (3) Personality and social competencies possessed by a certified elementary school teacher Physical Education been good with a percentage of 89.6%. Conclusions from this research is the performance Physical Education elementary teacher certified in Bradford County District Brits 2013 was a good year.